Information quality, performance measurement, and security demand in rational expectations economies - Thomas H. Noe; Buddhavarapu Sailesh Ramamurtie (Federal Reserve Bank of Atlanta, 1995)
The relationship between asset demand and information quality in rational expectations economies is analyzed. First we derive a number of new summary descriptive statistics that measure four basic characteristics of investment style: asset selection, market timing, aggressiveness, and specialization. Then we relate these statistics to the divergence between a given investor's information structure and the market average information structure. Finally, we demonstrate that informational differentials can be identified, and consistently estimated, using OLS from the time series of observed asset demand.
Keywords: 330; Rational expectations (Economic theory); Information theory